Ves' narod, vsya strana etoy trudnoy poroy pomogli tebe vystoyat', gorod-geroy! - Gal'ba, V; Romanova, M
Cartoon of Hitler, who is represented as a chain, being smashed by a Soviet sword Original title: весь народ, вся страна этой трудной порой помогли тебе выстоять, город-герой! Suggested translation: All the people, the whole country, this difficult sometimes helped you survive, hero city! PO-2246